Li7(BH)5+: a new thermodynamically favored star-shaped molecule1. Issue 29 (7th August 2015) - Torres-Vega, Juan J.; Vásquez-Espinal, Alejandro; Beltran, Maria J.; Ruiz, Lina; Islas, Rafael; Tiznado, William
<x xml:space="preserve">Abstract</x> The feasibility of stabilizing a new star-shaped molecule, the Li7(BH)5+, is demonstrated by an in silico investigation, combining DFT and Ab initio methods.